1995
DOI: 10.1227/00006123-199508000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Head Injury in Mice, Using a Fructose 1,6-Diphosphate and Dimethyl Sulfoxide Combination

Abstract: Mice were subjected to moderate (800 g/cm force) or severe (900 g/cm force) head injury and treated 5 minutes later with various compounds. Treatments consisted of intravenous administration of the following compounds: 1) fructose 1,6-diphosphate (FDP), 2) dimethyl sulfoxide (DMSO), 3) FDP + DMSO, and 4) vehicle nontreated. Sensory-motor evaluations 1 and 2 hours after 800 g/cm-force head injury showed that significant protection of motor function (grip test) was achieved with FDP + DMSO but not with treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Finally, DMSO, when co-administered with a candidate therapeutic, offers potential for synergism, by acting through separate and/or overlapping pathways. While we found no evidence of this in the current study, others have reported synergism in a model of brain ischemia where DMSO was either combined with fructose 1,6-disphosphate, an intermediate of anaerobic metabolism, or prostacyclin (PG I2 ) which blocks aggregation of platelets and functions as a vasodilator [12], [54].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Finally, DMSO, when co-administered with a candidate therapeutic, offers potential for synergism, by acting through separate and/or overlapping pathways. While we found no evidence of this in the current study, others have reported synergism in a model of brain ischemia where DMSO was either combined with fructose 1,6-disphosphate, an intermediate of anaerobic metabolism, or prostacyclin (PG I2 ) which blocks aggregation of platelets and functions as a vasodilator [12], [54].…”
Section: Discussioncontrasting
confidence: 85%
“…In summary, while this study and others [12], [13], [52], [54] underscore the potential utility of DMSO for the treatment of brain and SCI, there remain conflicting reports about the efficacy of DMSO. This is illustrated in recent studies reporting either no effects or reduced performance on behavioral tests after traumatic brain injury [55] and others suggesting improved learning ability in cerebellar mutant Lurcher mice [56].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition to its activity as a scavenger of ⅐OH (Reuvers et al, 1973), DMSO has been reported to regulate cell differentiation (Friend et al, 1971;Collins et al, 1978;Isom et al, 1985), the cell cycle (Darling et al, 1989;Sawai et al, 1990;Srinivas et al, 1991), and apoptosis (Marthyn et al, 1998;Fiore and Degrassi, 1999). Administration of DMSO to rodents and primates can reduce neuronal injury in experimental models of ischemic (Albin et al, 1983;de la Torre, 1983;Phillis et al, 1998) and traumatic brain injury (de la Torre, 1983(de la Torre, , 1995, improve cerebral blood flow after injury (de la Torre, 1983), and reduce intracranial pressure after head trauma (Karaca et al, 1991). It is conceivable that the DMSO structure plays important roles in the cellular, molecular, and pharmacological effects of serofendic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have used dimethyl sulfoxide (DMSO) in combination with GM6001 [10,11]. While DMSO is commonly used as a vehicle to increase solubility of a drug, it has been reported to have neuroprotective properties in traumatic brain injury and SCI [12,13]. The putative neuroprotective activity of DMSO is thought to arise from its ability to block voltage-sensitive sodium channels and calcium influx into cells, and mitigate opening of ionotropic channels that are activated by glutamate [14].…”
Section: Changes In Bladder Function Following Spinal Cord Injurymentioning
confidence: 99%